Cryptic species within the Tetratrichomonas gallinarum species complex revealed by molecular polymorphism - Cepicka, Ivan; Kutisová, Katerina; Tachezy, Jan; Kulda, Jaroslav; Flegr, Jaroslav (Veterinary parasitology, 2005)
Tetratrichomonas gallinarum is a widespread intestinal parasite of galliform and anseriform birds. The pathogenicity of this species is controversial, presenting an unsettled problem as yet. We analysed the polymorphism and genetic relationship among 29 isolates of T. gallinarum obtained from eight bird species and five T. gallinarum-like isolates from the oral cavity and lower respiratory tract of human patients. Two methods were used for the analyses: RAPD and sequencing of 16S rRNA, 5.8S rRNA, ITS1 and ITS2 genes, both producing consistent and well-supported results. The isolates were divided into five groups, A-E, with eleven subgroups. The distance between groups E, D and the cluster A-B-C considerably exceeded usual intraspecific polymorphism seen in trichomonads. Moreover, the largest subgroup, A2 (containing 18 isolates), was divided into three branches according to the host specificity. All isolates from humans were placed into avian subgroups A2 and B2. We conclude that our isolates represent, at least, three morphospecies or rather complexes of several cryptic species. Since certain species of the T. gallinarum complex can differ in their biological characteristics and some of them can infect humans, the problem of T. gallinarum pathogenicity should be re-examined with regard to specific genetic groups and zoonotic potential of some of these lineages should be considered.
Keywords: sekvenční seřazení; mezerníky ribozomální DNA; Trichomonas; technika náhodné amplifikace polymorfní DNA; Humans; sekvence nukleotidů; Trichomonas Infections; Phylogeny; Random Amplified Polymorphic DNA Technique; Molecular Sequence Data; molekulární sekvence - údaje; nemoci ptáků; protozoální DNA; RNA ribozomální 16S; Cluster Analysis; DNA, Protozoan; lidé; zoonózy; zvířata; RNA, Ribosomal, 5.8S; RNA, Ribosomal, 16S; Galliformes; trichomoniáza; Anseriformes; Base Sequence; fylogeneze; polymerázová řetězová reakce; shluková analýza; Polymerase Chain Reaction; Zoonoses; RNA ribozomální 5.8S; Animals; Bird Diseases; DNA, Ribosomal Spacer; Sequence Alignment